Paradoks pertumbuhan ekonomi Indonesia: Antara pembangunan infrastruktur dan ketimpangan sosial-ekonomi - Mardliyah, Imayatin (Maliki Interdisciplinary Journal, 2024)
This study aims to investigate the paradox of economic growth and socio-economic inequality in Indonesia. Research methods used include secondary data analysis, literature studies, regression analysis, case studies, surveys, and focus groups. The findings highlight factors such as non-inclusive development policies and inequality of access to economic opportunities as the main causes of this paradox. The implication is the need for more inclusive economic policy reform and the active participation of all parties in the policy-making process. This research provides a better understanding of this paradox and highlights the importance of concrete steps in addressing this issue to achieve more inclusive, sustainable, and equitable economic growth.